Soviet Legal Institutions: Doctrines and Social Functions - Grzybowski, Kazimierz (1962)
This book represents the highlight of a career of scholarship by its author and a most significant contribution to the literature, which will bring to those who seek it an understanding of the role law plays in Soviet Russia. More important, it will bring that understanding in a comparative context which sharpens the impact and compels a careful analysis of the social function legal institutions perform in both systems. Though Soviet jurists may deny the validity of comparative methodology as applied to the Soviet legal order, the analysis which is here presented proves not only that comparisons are possible but also that they can be most illuminating. In some respects it is a grim story which unfolds in this perceptive work. The Western mind is not unfamiliar with governmental efforts to shape human conduct through the creation or manipulation of legal institutions. We are not unmindful that the monopoly of force reserved to government can be turned, through the imposition of penal sanctions, to deter human conduct which would otherwise emerge as a result of other social pressures. But the Western mind will find the chapter on Homo Sovieticus extremely disquieting as the author traces the means by which and the extent to which the compulsive force of law is directed toward reshaping the ideas, the attitudes, the minds of the Soviet citizens. To read, from the Judicature Act of 1933, that courts of law shall educate the citizens of the USSR in the spirit of devotion to the country and the cause of socialism ... cannot but evoke in the Western mind a response of shock, when one recalls the power of the court to enforce its dictates. To watch the concept of public official being expanded through legal manipulation to include practically an entire population, while simultaneously observing that the state is imposing a stringent liability upon public officials who deviate from current political or economic views, will not be restful. To learn that libel suits have disappeared from the dockets of socialist courts because the press now represents functionally the best way to attack problem spots in the social and economic life and must not be impeded by individual interests from pursuing social action, will not appeal to those who champion freedom of the press. But this book is not written to shock the reader. It is written to bring him enlightenment concerning the realities of legal order in Russia. Not many persons could write it. To do so requires a deep understanding of several legal systems, a capacity to translate the verbal doctrine into terms of social function, and an ability to perceive those points of comparison which will permit the reader to understand the human meaning of legal institutions. The distinguished author, Dr. Kazimierz Grzybowski, has all these qualifications and he has brought them to bear in full measure to produce this volume.https://repository.law.umich.edu/michigan_legal_studies/1025/thumbnail.jp